PREPARATION AND CHARACTERIZATION OF ACTIVATED CARBON FROM BABUL (ACACIA ARABICA) AND COCONUT SHELLS BY PHYSICAL ACTIVATION IN A FLUIDIZED BED REACTOR - Usmani, Tanzil H; Motan, M Tahir; Mumtaz, M; Ahmed, M Aleem (Biological Sciences - PJSIR, 2003)
Two indigenous raw materials Babul (Acacia arabica) and coconut shells were subjected to physical activation for the preparation of activated carbon by a mixture of superheated steam and air in a S.S. fluidized bed reactor. The influence of various operational variables like particle size of the two raw materials, time of activation and pressure of the fluidizing gas on different physical and chemical properties of the Granular Activated Carbon (GAC) samples was investigated. Different operational parameters being optimized in this study were particle size of 1.00 – 2.00 mm, operating pressure of 20 psi in 75 min time of activation. Babul was however not found to be an appropriate precursor for preparing GAC, probably due to its low inherent strength, eventually resulting in quite low yield and ball pan hardness of GAC samples. Further it was concluded, that GAC in quite a good yield and adsorptive capacity in liquid as well as vapour phase systems and standard hardness was obtained from coconut shells and it was much superior, when compared with the product obtained from Babul.